2021
DOI: 10.1017/s1742170521000132
|View full text |Cite
|
Sign up to set email alerts
|

Do cost-share programs increase cover crop use? Empirical evidence from Iowa

Abstract: Cover crops can generate both on-farm and water-quality benefits. However, their use in Iowa remains subdued, partly due to implementation costs faced by farmers. We tested the hypothesis that monetary incentives through cost-share programs are effective at increasing the area of farmland planted to cover crops in Iowa, as opposed to the alternative in which the participants of cost-share programs would have planted the same cover-crop acreage in the absence of payment. We found that cost-share payments induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…The results of this study, as shown in Table 5, revealed the absence of any significant correlation between the entrepreneurs’ age and firms' TE. These result, however, is supported by the findings of Thapa (2015), Sawadgo and Plastina (2020) and Adnan et al (2021). One potential explanation in this study's context is that the activities' nature is similar for older and younger entrepreneurs.…”
Section: Resultssupporting
confidence: 73%
“…The results of this study, as shown in Table 5, revealed the absence of any significant correlation between the entrepreneurs’ age and firms' TE. These result, however, is supported by the findings of Thapa (2015), Sawadgo and Plastina (2020) and Adnan et al (2021). One potential explanation in this study's context is that the activities' nature is similar for older and younger entrepreneurs.…”
Section: Resultssupporting
confidence: 73%
“…Moving forward, it seems that focusing policy attention toward studying, strengthening, and/or implementing other policy mechanisms has a better chance to more immediately impact cover crop uptake. For instance, given the statistically significant effect of EQIP payments on cover crop adoption observed in past studies (Fleming, 2017;Lee & McCann, 2019;Lichtenberg, 2014;Mezzatesta et al, 2013;Sawadgo & Plastina, Forthcoming), it seems that improved targeting of cost-share and/or direct subsidy payments (as well as overall strengthening of these types of programs at the state or federal level) would have a more meaningful effect on cover crop adoption. Farm payments through carbon markets may also results in more meaningful impacts on cover crop use.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…For example, farmers who were already using cover crops on at least 40 ha increased their average cropland with cover crops 52% from 158 to 240 ha during the period of program participation. Although we did not estimate additionality (i.e., adoption that would not have occurred in the absence of incentive programs), previous research on cover crop incentive programs estimated additionality rates ranging from 54% in Iowa (Sawadgo & Plastina, 2021) to 91% in Ohio (Messatesta et al, 2013). Most respondents who had participated in an incentive program were still actively enrolled in a program when the survey was completed.…”
Section: Program Impactmentioning
confidence: 99%